PROMOSI KESEHATAN GIGI DENGAN MEDIA GAME KARPET (KARTU PERTANYAAN ) TERHADAP PENGETAHUAN SISWA/I SDN 06093 MEDAN - Rawati Siregar; Sri Junita Nainggolan; Aminah br. Saragih (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Oral health is an important part of general health. Oral health has a negative impact on body development and quality of life and oral hygiene causes tooth decay. The success of maintaining oral health can also depend on knowledge. Knowledge of oral health in children will affect the behavior of maintaining dental health in children. This type of research is quantitative with a quasi experiment and uses univariate and bivariate data analysis with the Wilcoxon test. . The sample in this study was a minimum sample of 30 respondents in grade VI students of SDN 060934 Jl Luku II Kec. Medan Johor with a sampling technique using total sampling. This research was conducted in October 2024. using univariate and bivariate data analysis with the Wilcoxon test. The results of the statistical test of this study showed that there was a significant difference in increasing knowledge between before and after counseling using carpet media (question cards) with a p value <0.05. The conclusion of this study is that health promotion using carpet games (question cards) is effective in increasing dental and oral health knowledge in students. It is recommended that schools make dental health education programs more interesting by providing health education, so that student behavior and knowledge become better and of higher quality